Manure storage operations mitigate nutrient losses and their products can sustain soil fertility and enhance wheat productivity. (1st July 2019) - Ali, Basit; Shah, Ghulam Abbas; Traore, Bouba; Shah, Syed Ansar Abbas; Shah, Shamim-ul-Sibtain; Al-Solaimani, Samir Gamil Mohammad; Hussain, Qaiser; Ali, Nadeem; Shahzad, Khurram; Shahzad, Tanvir; Ahmad, Afzal; Muhammad, Sher; et al.
Abstract: Livestock manure is a valuable source of nutrients for plants. However, poor handling practices during storage resulted in nutrient losses from the manure and decrement in its nitrogen (N) fertilizer value. We explored the influence of divergent storage methods on manure chemical composition, carbon (C) and N losses to the environment as well as fertilizer value of storage products after their application to the wheat. Fresh buffalo manure (FM) was subjected to different storage operations for a period of ∼6 months, (i) fermentation by covering with a plastic sheet (CM) (ii) placed under the roof (RM) (iii) heap was unturned (SM) to remain stacked at an open space and (iv) manure heap turned monthly (TM) to make compost. During storage, 8, 24, 45 and 46% of the initial Ntotal was lost from CM, RM, SM, and TM, respectively. The respective C losses from these treatments were 16, 34, 47 and 44% of the initial C content. After stored manures application to the wheat crop, mineral N in the soil remained 27% higher in CM (14.1 vs. 11.1 kg ha −1 ) and 3% (10.8 vs. 11.1 kg ha −1 ) lower in SM compared to FM treatment. In contrast, microbial biomass C and N was 35 (509 vs.782 mg C kg −1 soil) and 25% (278 vs.370 mg N kg −1 soil) lower in CM than FM treatment, respectively indicating lower N immobilization of CM in the soil. These findings could result in the highest grain yield (5166 kg ha −1 ) and N uptake (117 kg ha −1 ) in CM and the lowest in SM treatments (3105 and 61 kg ha −1, respectively). Similarly, wheat crop recovered 44, 15 and 13% N from CM, TM and SM, respectively. Hence, management operations play a critical role in conserving N during storage phase and after stored manure application to the field. Among the studied operations, storing animal manure under an impermeable plastic sheet is a much better and cheaper option for decreasing N losses during storage and improving wheat yield when incorporated into the soil. Therefore, by adopting this manure storage technique, farmers can improve the agro-environmental value of animal manure in Pakistan. Highlights: Storage methods impact on C and N losses from animal manure (M) was tested. These losses were lower in anaerobic (CM) than turned (TM) or unturned (SM) storage techniques. Mineral N and P content was higher in CM applied soil than SM and fresh manure (FM). Soil microbial biomass C and N was higher in FM treatment than CM, SM or TM. Wheat grain yield and N uptake were the highest in CM and the lowest in SM treatment.